Efecto del sexo y edad de sacrificio sobre la composición tisular y composición regional de la canal de cuy. - Palacios Sotomayor, Dayana Maite (2017)
The content of the muscle tissue fat and bone are the main features that contribute to the commercial of any animal’s carcass. The animal gender plays a fundamental role. For example, castrated males and females have frequently more greased carcass. Furthermore, as the animal becomes older, the muscular tissue and bones are developed first and fat is a late deposition tissue. There is no much information about the regional and tissue composition of a guinea pig’s carcass as well as the effect of the animal’s gender and age on the tissues named before. It explains the objective of this paper, which is to analyze the effect that the gender and age of the animal have on the regional and tissue composition of the animal’s carcass. For this paper, 120 guinea pigs have been used, which have been sacrificed within the first 3,4 and 6 months of life. The animals have been sacrificed according to well-established standards. The dissection has been carried out in the left hemicanal divided into four standardized pieces. The percentage of tissue for each piece has been calculated. The ANOVA process for repeated measures has been used for analyzing within effects, while simple ANOVA process for between effects. The most relevant results show that the percentage of muscle tissue is the greatest in every piece, followed by bone and skin. The dispossession and fat between muscle have the smallest percentage of all pieces. In addition, females show off the biggest fat percentage compared to males. Just males from 4 to 6 months have a greater percentage of muscle tissue in the neck, compared to females. Within the age from 3 to 6 months, females increase their fat percentage in the legs and spare ribs, meanwhile the bone percentage in every piece was reduced. As males get older, there is a certain proportion of tissues that increases equally in them, except the muscle increased in the arms and the fat increased in the spare ribs. In conclusión, the muscle tissue shows bigger percentages for all pieces, ages and genders. There is an effect in the proportion of different tissues due to the age of the animal and it is affecting more to females than males.